2017
DOI: 10.3390/nu9070692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbohydrate and Glutamine Supplementation on Oral Mucosa Immunity after Strenuous Exercise at High Altitude: A Double-Blind Randomized Trial

Abstract: This study analyzed the effects of carbohydrate and glutamine supplementation on salivary immunity after exercise at a simulated altitude of 4500 m. Fifteen volunteers performed exercise of 70% of VO2peak until exhaustion and were divided into three groups: hypoxia placebo, hypoxia 8% maltodextrin (200 mL/20 min), and hypoxia after six days glutamine (20 g/day) and 8% maltodextrin (200 mL/20 min). All procedures were randomized and double-blind. Saliva was collected at rest (basal), before exercise (pre-exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In the PATHWAY analysis, the most closely related to the differentially methylated genes in breast cancer tissues was the ‘D-Glutamine and D-glutamate metabolism’. Glutamine is an important fuel for the immune system and has important immunomodulatory effects ( 25 ), which can promote the division and differentiation of lymphocytes and macrophages. Exogenous glutamine can significantly increase the number of lymphocytes, T lymphocytes and CD4/CD8 ratio in critically ill patients and enhance the body immunity ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the PATHWAY analysis, the most closely related to the differentially methylated genes in breast cancer tissues was the ‘D-Glutamine and D-glutamate metabolism’. Glutamine is an important fuel for the immune system and has important immunomodulatory effects ( 25 ), which can promote the division and differentiation of lymphocytes and macrophages. Exogenous glutamine can significantly increase the number of lymphocytes, T lymphocytes and CD4/CD8 ratio in critically ill patients and enhance the body immunity ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal and human studies have demonstrated glutamine ability to attenuate inflammatory mediators released in injury and stress conditions. Few studies have evaluated the effects of glutamine supplementation on hypoxia, mood and cognition [8,9,[76][77][78][79]. Therefore, we intend to demonstrate the influence of glutamine supplementation on inflammation and subsequently concerning these two psychobiological factors.…”
Section: Glutamine Inflammation Mood and Cognitionmentioning
confidence: 98%
“…Glutamine is a crucial energy fuel for rapidly growing cells (mostly immune and enterocytes cells), the precursor of glucose, proteins and nucleic acids, having diverse roles in the organism, being key to the synthesis of cytokines, hormones, acid-base balance, transport of ammonia and cell proliferation [5]. Glutamine supplementation has been studied to reduce the risk of upper respiratory tract infections (URTI) after long-term exercise (i.e., marathon), thus improving immunocompetence in normoxia [6] and hypoxia [7][8][9]. The high blood glutamine availability can interfere with central glutamate synthesis, an excitatory neurotransmitter that stimulates ventilation, increasing O 2 saturation (SaO 2 %) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study authors suggested this was the result of an inflammation response in the lungs or vascular dysfunction due to exposure to airborne particles. 12 Cigarette smoke and secondhand smoke, 13 weight gain, 14,15 drinking alcohol, 16,17 living at high altitude, or too much or too little exercise 18,19 are other factors that deprive the body of optimal oxygen levels.…”
Section: Causes Of Hypoxiamentioning
confidence: 99%
“…Oxygen serves as a fuel for cytochrome oxidase, the final enzyme in the electron transport chain that generates ATP. 18 Because diffusion would be an inefficient means of supplying cells with oxygen, hemoglobin and myoglobin act as oxygen-carrying molecules to perfuse the tissues. 20 As blood circulates through capillaries, oxygen bound to hemoglobin diffuses via a steep pressure gradient into tissues and subsequently into the mitochondria.…”
Section: Low Oxygen and Mitochondriamentioning
confidence: 99%